EDUKASI PENYAKIT MENULAR SEKSUAL HIV DAN AIDS BERSAMA SISWA SMK NEGERI 1 TUBAN - Arifin, Mohammad Fahrul Arifin; fauziansyah, ahmad; karyo; ubaidillah faqih, Muhammad (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
HIV (Human Immunodeficiency Virus) is a virus that can cause AIDS by attacking white blood cells called CD4 cells, so it can damage the immune system. AIDS (Acquired Immuno Deficiency Syndrome) or a collection of various disease symptoms resulting from a decrease in an individual's immune system due to HIV. In 2014, Indonesia was listed as a country that received a red report card from The Joint United Nation Program On HIV/AIDS (UNAIDS). This is because Indonesia is considered to pay less attention to HIV/AIDS patients and the mortality rate of HIV/AIDS sufferers in Indonesia is still relatively high.